UJI PERFORMANSI POMPA HYDRAM DALAM PENYEDIAAN AIR BERSIH KELOMPOK USAHA BON BELOK KOPI DAN BANJAR ADAT BON DESA BELOK/SIDAN - Suarda, M.; Suaniti, N.M.; Sucipta, M.; Suweden, N.; Dwijana, I.G.K.; Widiarta, I.P. (Buletin Udayana Mengabdi, 2023)
This paper examined the performance of the hydraulic ram pump that has been designed and installed to meet the clean water needs of the 'Bon Belok Kopi' Business Group and several families of Bon traditional community in Belok/Sidan Village, Petang District, Badung Regency, Bali Province. This business group is shortage to clean water in the process of processing their coffee production so that the community relies on rainwater and buys water from tank cars at a price of sixty thousand rupiah per cubic meter. Likewise, the Bon traditional community experienced the same problem, especially for their traditional activities. This problem has an impact on the capacity, quality and cost of coffee production of the business group, as well as the cleanliness, health and economy of the Bon traditional community. In the Bon area, there is a spring in the garden area belonging to the head of the business group with a flow rate of 3 liters/second at an elevation of 1024 m.swl, while residential areas are located at an elevation of 1135 m.swl. The hydraulic ram pump has been designed, built, installed and operated. The hydraulic ram pump performance test has been carried out on five variations of the pumping head. At a pumping head of 70 m, at the location of coffee processing, it produces a pumping flow of 8.84 m 3 /day with the pump efficiency of 71%. Meanwhile, at the highest pumping head of 110 m, at Puncak Bon Temple, it produces a pumping discharge of 5.04 m 3 /day with the pump efficiency of 59%. Keywords: Hydram pump, pump performance, Bon Belok Kopi, Bon traditional community.